Pengaruh Financial Literacy, Financial Knowledge, Financial Attitude, Income dan Financial Self Efficacy terhadap Financial Management Behavior Entrepreneur Lulusan Perguruan Tinggi di Surabaya - Anglia Dinda Pramedi; Nadia Asandimitra Haryono (Jurnal Ilmu Manajemen, 2021)
Finance is one of the factors in the development of a business. Therefore, the entrepreneur should be able to handle finances well to reach business purposes. Based on the previous studies, the purpose of this research is to determine the effect of several factors such as financial literacy, financial knowledge, financial attitude, income, and financial self-efficacy on financial management behavior. The research sample is 211 entrepreneur who has graduated from college in Surabaya. This research used conclusive causality research with primary data. The sampling technique used purposive sampling and snowball sampling method, and data distribution using an online questionnaire. SEM (Structural Equation Model) used for data analysis technique and using AMOS 24. The hypothesis showed that financial knowledge, income, and financial self-efficacy did not affect financial management behavior, but financial literacy and financial attitude influence financial management behavior. Therefore, the entrepreneur needs to improve financial literacy and financial attitude to manage finance on the business better.